Strategi Komunikasi Efektif Motor Honda dalam Branding, Marketing dan Selling Produk - Sukma, Agus Hitopa; Misnan, Misnan; Hiswanti, Hiswanti; Pranawukir, Iswahyu; Barizki, Rezzi Nanda (Jurnal Publisitas, 2024)
The automotive industry in Indonesia is currently very competitive, with various brands competing for consumers' attention. In this situation, an effective communication strategy is the key to building a brand, marketing products and increasing sales. This research aims to analyze the communication strategies used by PT. Astra Honda Motor (AHM) in branding, marketing and selling Honda motorbike products in Indonesia. This research uses a qualitative method with a case study on AHM. Data was collected through interviews with key informants at AHM, observation and document analysis. The research results show that AHM uses various effective communication strategies in branding, marketing and selling Honda motorbike products. Branding strategy includes establishing a strong brand image. AHM has built Honda's brand image as a quality, fuel efficient and sporty motorbike. This is done through various communication activities, such as advertising, sponsorship and events. The marketing strategy is carried out through integrated marketing. This strategy includes: 1) Above-the-line communication: AHM uses various advertising media such as TV, radio, print media and online media to build brand awareness and increase consumer interest in Honda motorbike products. 2) Below-the-line communication: AHM uses various promotional activities such as exhibitions, events and sponsorships to increase sales of Honda motorbike products. 3) Digital marketing: AHM utilizes digital media such as websites, social media and mobile applications to reach a wider range of consumers and establish more personal interactions with consumers. The selling strategy prioritizes personal selling. AHM has an extensive dealer network throughout Indonesia. These dealers provide quality sales and after-sales services to consumers.